Pengembangan E-Modul Pembuatan Pola Blus pada Fase E di SMKN 1 Brondong - Giry Muliana Ramdhani; Mita Yuniati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to develop an e-module learning media for the elements of the fashion production process, and to assess the feasibility of the material, media, and language by relevant experts. The research method used in this study is R&D with the ADDIE model approach, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used questionnaires and tests. The questionnaires, in the form of instrument validation sheets, were distributed to material experts, media experts, and language experts, using indicators of good e-module characteristics. Test data collection included cognitive and psychomotor assessments. The results of this study indicated that the material feasibility was 90%, the media feasibility was 87%, and the language feasibility was 92%. Furthermore, student learning outcomes through cognitive and psychomotor tests showed a score of 90%. Therefore, the overall assessment of the blouse pattern-making e-module was categorized as